Why is alexithymia a risk factor for affective disorder symptoms? The role of emotion regulation - Preece, David; Mehta, A.; Becerra, R.; Chen, Wai; Allan, A.; Robinson, K.; Boyes, Mark; Hasking, Penelope; Gross, J.J. (ELSEVIER, 2022)
Background: Ever since alexithymia was defined in the 1970s, robust associations have been observed between alexithymia and a variety of symptoms of psychopathology. Alexithymia is now widely regarded as an important transdiagnostic risk factor, and it is frequently assessed in clinical and research settings. However, despite this strong interest, it remains unclear exactly why (i.e., by which mechanisms) alexithymia is linked to psychopathology. In this paper, we hypothesise that alexithymia is linked to affective disorder symptoms because alexithymia impairs people's ability to regulate their emotions, and we empirically test this hypothesis. Method: We administered a battery of psychometric measures to 501 adults in the United States, and examined the direct and indirect effects between alexithymia (Perth Alexithymia Questionnaire), emotion regulation ability (Perth Emotion Regulation Competency Inventory), and affective disorder symptoms (Depression Anxiety Stress Scales-21). Results: In the Pearson bivariate correlation matrix, alexithymia, emotion regulation difficulties, and affective disorder symptoms were all significantly correlated. In the modelling of direct and indirect effects, alexithymia was indirectly associated with affective disorder symptoms through emotion regulation difficulties (no significant direct effect). Limitations: Our online survey data were all self-report data and cross-sectional. Future longitudinal work would be beneficial. Conclusions: Our findings support contemporary theorising that alexithymia is linked to affective disorder symptoms via emotion regulation difficulties. These results help to clarify the mechanisms by which alexithymia may predispose people to affective disorder symptoms, and highlight the importance of considering the roles of alexithymia and emotion regulation in case conceptualisations and treatment planning.